I Would Rather Die Than Live Sedentary: Is the Demonization of Passive Leisure Creating a Future Generation of Older People Who Will Not Accept Inactivity?. Issue 3 (July 2017) - Dionigi, Rylee A.
Abstract : This critical reflection discusses some potential positive and negative implications, with particular focus on the latter, of the promotion and participation of sport and physical activity to older people. Reflecting upon my 15 years of research on older Masters athletes (and active older people in general), I argue that the field of sports/exercise sciences needs to change its framework for leisure engagement (or physical activity) for current and future cohorts of older adults from one of blaming inactivity for disease, to a framework that values all forms of leisure, from passive to active, mental to social, etc, and one that accepts difference and diversity in aging.